Functional ligands for improving anticancer drug therapy: current status and applications to drug delivery systems - Rajiv Bajracharya; Jae Geun Song; Basavaraj Rudragouda Patil; Sang Hoon Lee; Hye-Mi Noh; Da-Hyun Kim; Gyu-Lin Kim; Soo-Hwa Seo; Ji-Won Park; Seong Hoon Jeong; Chang Hoon Lee; Hyo-Kyung Han (Taylor & Francis Group, 2022)
Conventional chemotherapy lacking target selectivity often leads to severe side effects, limiting the effectiveness of chemotherapy. Therefore, drug delivery systems ensuring both selective drug release and efficient intracellular uptake at the target sites are highly demanded in chemotherapy to improve the quality of life of patients with low toxicity. One of the effective approaches for tumor-selective drug delivery is the adoption of functional ligands that can interact with specific receptors overexpressed in malignant cancer cells. Various functional ligands including folic acid, hyaluronic acid, transferrin, peptides, and antibodies, have been extensively explored to develop tumor-selective drug delivery systems. Furthermore, cell-penetrating peptides or ligands for tight junction opening are also actively pursued to improve the intracellular trafficking of anticancer drugs. Sometimes, multiple ligands with different roles are used in combination to enhance the cellular uptake as well as target selectivity of anticancer drugs. In this review, the current status of various functional ligands applicable to improve the effectiveness of cancer chemotherapy is overviewed with a focus on their roles, characteristics, and preclinical/clinical applications.